Estopô Balaio, a case of a socio-political engaged approach to Applied Theatre - Juliana Spadotto; Nadia Saito (Revista nuestrAmérica)
Theatre can play a social transformation role when used as a platform for empowering individuals who are critically engaged in such cultural practices. This article is part of a research conducted in 2021 on Estopô Balaio's work - a Brazilian collective theatre group that has worked in an under-represented community in São Paulo. This research aims to critically demonstrate how Applied Theatre (AT) can transform people's lives, empower individuals engaged in group activities, and build a sense of community and empathy. Moreover, two Brazilian authors, Paulo Freire (1970) and Augusto Boal (2019), were used as primary references. The methodology framework was chosen to depict how the research was conducted during the pandemic. The Brazilian cultural and social context during COVID-19 will be portrayed shortly to present the research problem and purpose.